IMPLEMENTASI KEBIJAKAN PENDIDIKAN DAN PELATIHAN KEPALA DESA PADA BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA KABUPATEN DONGGALA - Tirtaprima, Riski (Katalogis, 2017)
This study aims to determine the implementation of Education and Training for Village Heads Policy at the Village Governance and Society Empowerment Board of Donggala Regency. The research type of this study is descriptive qualitative research. The informants in this study were 5 people. The determination of informants in this study was using purposive method. The type of data used in this study was primary and secondary data. The analysis of data used in this study was using Miles and Huberman, namely data reduction, data presentation, and conclusion. The theory used in this study was the theory of Donald S. van Meter and Carl E. van Horn consisting of six aspects: Policy Standards and Targets, Resources, Interagency Communications, Characteristics of Implementing Agency (Bureaucracy Structure), Tendencies/Attitudes (Dispositions), and Social, Economic, and Political Conditions. In the implementation of this study, the researcher only focused on five aspects that were assumed to be in accordance with the phenomena that appeared at the time of this study: Policy Standards and Targets, Resources, Interagency Communications, Characteristics of Implementing Agency (Bureaucracy Structure), and Tendencies/Attitudes (Dispositions). Implementation of Education and Training for Village Heads Policy in general must to be improved continuously considering that the program goals was to improve the knowledge and skills of village heads in performing their duties and functions as the spearhead of national and regional development. Of course, in practice, the support of adequate resources is necessary, both human resources that have the ability to understand what their responsibilities in carrying out the process of policy implementation, and non-human resources such as facilities and infrastructures so that these elements can contribute maximally in the implementation process. In addition, to facilitate the implementation process, it should also has good and sustainable communication and cooperation the implementation process, where a good communication comes from a positive cooperation between government officials, in this regard the employees of the Village Governance and Society Empowerment Board of Donggala Regency. Thus, the researcher concludes that the implementation of Education and Training for Village Heads Policy had not run as expected.